Routine activity and victimization at work - Lynch, James P. (Journal of quantitative criminology, 1987)
This paper introduces the idea of “domain-specific” models of victimization as a means of improving the fit between theoretical concepts in routine activity theory and available data. Peoples' activity and their victimization experience can be divided into domains such as work and leisure. This paper focuses on the work domain. It demonstrates that activities performed as part of the occupational role affect the risk of victimization at work to a much greater degree than demographic characteristics of workers. These findings provide support both for routine activity theory generally and for domain-specific models as a particular approach to testing the theory.